Sámi Archaeology and Postcolonial Theory - An Introduction - Spangen, Marte; Salmi, Anna-Kaisa; Äikäs, Tiina (Arctic Anthropology, 2015)
While researchers within Sámi archaeology have dealt with issues closely related to postcolonial theory and critique since the 1970s onwards, this has rarely been done with explicit mention or coherent use of this theoretical complex. This somewhat paradoxical situation was addressed in a session at the 14th conference of the Nordic Theoretical Archaeology Group at Stockholm University in April 2014, an initiative that eventually resulted in the present collection of articles. In this introduction we briefly present the historiographical and discursive background for the debates that are outlined in the following contributions.